Geoheritage and Geodiversity Assessment Framework for Practical Application to Geoconservation of the Coromandel Peninsula, New Zealand - Vladyslav Zakharovskyi; Karoly Nemeth; Ilmars Gravis; Chris Twemlow (Geoconservation Research)
Life on Earth is influenced by abiotic nature, providing resources and shelter for living beings on the Earth. Hence, this part of nature should be well treated and protected. Study of geodiversity can facilitate education about abiotic nature and processes occurring around us. Geodiversity as a discipline is relatively young, but worthy of more attention and development. As well as a stand-alone scientific field, it may draw on other scientific disciplines in understanding the connection between natural materials and abiotic processes. Our research explores the paradigm of geodiversity and defines its meanings and elements. This will help us make the first steps in developing a methodology of assessment of geodiversity for any type of territory on our planet. This article provides a conceptual framework, which is based on detailed description of the methodology. Additionally, it will build a better understanding about the connections between abiotic and biotic factors in the environment, and human society within that environment. Here we provide a globally applicable method, using the Coromandel Peninsula as a case study. Coromandel Peninsula is in the north part of the North Island of New Zealand. This environmentally diverse and ecologically rich region is shaped by interactions between volcanic activities and terrestrial/shallow marine sedimentation, potentially providing a rich geodiversity. A systematic table defining the elements of geodiversity is the main product of our research, and we demonstrate how these elements can be assessed in a simple way to define values of facets of abiotic nature, ultimately resulting in a holistic, integrated, and complete view of our unliving environment. This study is an initial step in building a common system for assessment of geodiversity of any part of our world using the most available data and records as a foundational database.